Serum Vitamin D Level and the Risk of Urinary Tract Infection in Children: A Systematic Review and Meta-Analysis - Li, Xiaoyan; Yu, Qing; Qin, Feng; Zhang, Biyu; Lu, Yanming (Frontiers in Public Health, 2021)
This systematic review and meta-analysis aimed to evaluate the association between serum vitamin D concentration and the risk of urinary tract infection (UTI) in children. Human studies reported the serum vitamin D level in children with UTI and healthy controls were collected from PubMed, Scopus, Embase, and Cochrane databases. The strictly standardized mean difference (SSMD) and 95% confidence interval (CI) were calculated to evaluate the relationship between serum vitamin D levels and risk of UTI. The results of analysis showed that serum vitamin D levels in children with UTI were significantly lower than healthy control children (SSMD: 0.891, 95% CI: 0.707–1.075, p < 0.000; SSMD: 0.797, 95% CI: 0.500–1.094, p < 0.000, respectively). It can be concluded that there is a significant negative relationship between serum vitamin D level and risk of UTI in children.